2013 Third International Conference on Advanced Computing and Communication Technologies (ACCT) 2013
DOI: 10.1109/acct.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Wormhole Attack Avoidance Technique in Mobile Adhoc Networks

Abstract: Security is an essential service for wired and wireless network communication. This work concerned with a particularly sever security attack that affects the ad hoc networks routing protocols, called "wormhole attack". There are many solutions to detect and prevent this attack like packet leashes, cluster base, hop count analysis etc., but none of them is perfect solution. This paper contains a proposal for new technique for wormhole avoidance. Proposed technique has been implemented with NS2 simulator over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In [17] contains a proposition for new strategy for wormhole evasion. Tha proposed method has been executed with the NS2 test system over the DSR protocol.…”
Section: Literature Surveymentioning
confidence: 99%
“…In [17] contains a proposition for new strategy for wormhole evasion. Tha proposed method has been executed with the NS2 test system over the DSR protocol.…”
Section: Literature Surveymentioning
confidence: 99%
“…Tunnel can be established between nodes by Packet Encapsulation, out of band hidden channel and high transmission power [11].…”
Section: Deployment Of Wormhole Attackmentioning
confidence: 99%
“…When wormhole nodes are introduced in the network, they try to validate its neighbouring nodes that they are its legitimate neighbours and the route through these nodes also exist. [1] In the figure 1, it is shown that when source and sink want to communicate, S-A-B-C-D route is followed which is a normal route. When wormhole nodes X and Y are introduced into the network, they lure their neighbours S and D that they are their immediate neighbours and have a path between X and Y.…”
Section: Wormhole Attackmentioning
confidence: 99%